Does Fiscal Austerity Affect Political Decision-Makers' Use and Perception of Performance Information?. Issue 3 (2nd July 2016) - Bjørnholt, Bente; Bækgaard, Martin; Houlberg, Kurt
ABSTRACT: This article investigates whether the fiscal environment that politicians face influences their use of performance information. It poses two competing hypotheses, suggesting that fiscal austerity either increases politicians' use of performance information, because they are more concerned about keeping up good performance in times of austerity, or decreases their use, because balancing the books is more vital in times of austerity, and therefore keeping within the budget gains political emphasis relative to sustaining good performance. The link between fiscal austerity and politicians' use of performance information is tested using survey and documentary data from Danish municipalities. The article concludes that politicians who face high fiscal austerity use performance information to a lesser extent than colleagues who face less fiscal austerity, thus indicating the use of performance information is "the politics of good times."